Monitoring GLP compliance: history and OECD framework - Sigman, Richard (Henry Stewart Talks, 2012)
1981 OECD Council Act on Mutual Acceptance of Data (MAD), Objectives and benefits of MAD, 1989 Council Act on Compliance Monitoring, Guidance on compliance monitoring, OECD Working Group on GLP, Exchanging information across countries